Misreadings of ‘judge not’ in contemporary discourse - Kayumba, Paul L. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
In contemporary discourse, Matthew 7:1 (‘Judge not, that you be not judged’) is frequently misused to justify absolute tolerance and moral relativism, thereby undermining the biblical call for moral discernment. This article contends that Matthew 7:1–6 does not prohibit judgement altogether but rather warns against hypocritical and self-righteous judgement, while affirming the necessity of righteous and humble discernment. The argument unfolds in three main components: (1) a close exegetical analysis of the Greek text, paying attention to its literary and rhetorical features; (2) a theological reflection rooted in Reformed tradition and informed by canonical and intertextual insights; and (3) a practical-pastoral engagement with contemporary cultural and ecclesial misappropriations of the text. By tracing intertextual connections with Old Testament wisdom literature (e.g. Pr 1:7; 9:8; 26:4–5), the article demonstrates that Jesus’s call for discernment is deeply rooted in the biblical tradition that affirms moral evaluation tempered by humility and wisdom. Ultimately, the article argues that Matthew 7:1–6 envisions a redemptive form of judgement – grounded in personal repentance and theological wisdom – that enables the church to engage the world with compassionate, courageous, and gospel-shaped ethical witness. Contribution: This article contributes to Reformed scholarship by reframing Matthew 7:1–6 as a theological model of restorative discernment. It advances the discussion by integrating rigorous exegesis, canonical and intertextual analysis, and theological synthesis, while addressing contemporary misappropriations of the text. In doing so, it equips the church to embody a cross-shaped ethic of truth and mercy in both its communal and public witness.